2008
DOI: 10.1007/s11274-008-9932-y
|View full text |Cite
|
Sign up to set email alerts
|

Screening of white rot fungi for biobleaching of Acacia oxygen-delignified kraft pulp

Abstract: To reduce the levels of chlorine-based chemicals in Acacia kraft pulp, we sought to isolate white rot fungus strains that could be used for biobleaching. For this purpose, we collected 600 fungal sources from Indonesia and subjected them to a three-step screening method. The first step involved culturing the strains on Acacia mangium wood powder, guaiacol and agar (WGA) medium. Of the 600 sources, 258 strains grew on WGA medium and generated a red color. The second step revealed that 31 of the 258 strains coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
8
2
Order By: Relevance
“…To the best of our knowledge, information about the bleaching and kappa number reduction of kraft pulp treated with Phlebiopsis spp. had not been previously reported, and we found that this taxa could be as efficient for kappa number reduction (48.3%, Table 3) as the well-studied white-rot species of the genera Trametes, Phanerochaete, and others (Takano et al 2001;Afrida et al 2009). Even the kappa number reductions obtained with the CMU-84/13 strain of I. lacteus were comparable to previously reported values (Table 3).…”
Section: Kraft Pulp Modifications Originated By Fungal Strainssupporting
confidence: 88%
See 2 more Smart Citations
“…To the best of our knowledge, information about the bleaching and kappa number reduction of kraft pulp treated with Phlebiopsis spp. had not been previously reported, and we found that this taxa could be as efficient for kappa number reduction (48.3%, Table 3) as the well-studied white-rot species of the genera Trametes, Phanerochaete, and others (Takano et al 2001;Afrida et al 2009). Even the kappa number reductions obtained with the CMU-84/13 strain of I. lacteus were comparable to previously reported values (Table 3).…”
Section: Kraft Pulp Modifications Originated By Fungal Strainssupporting
confidence: 88%
“…Solid-state fermentation assays for evaluating kraft pulp bleaching are usually conducted in Erlenmeyer flasks involving liquid cultures for inoculum preparation (Katagiri et al 1995;Afrida et al 2009), but this approach becomes complicated when handling large numbers of strains. Simpler solid-state fermentation bleaching assays, based on incubating strains directly on kraft pulp in a Petri dish, allow for daily visual corroboration of the progress of the bleaching process.…”
Section: Kraft Pulp Modifications Originated By Fungal Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…versicolor (NBRC 30340) and P. chrysosporium (NBRC 31249) were provided by the National Institute of Technology and Evaluation (NITE) Biological Resource Center (NBRC, Japan). I. lacteus KB-1.1 and L. tigrinus LP-7 were isolated and identified as described elsewhere [14]. All fungi were maintained at 30°C on agar slants containing 0.2% Acacia mangium wood powder, 0.01% guaiacol, and 1.6% potato dextrose agar (PDA).…”
Section: Tmentioning
confidence: 99%
“…Therefore, two fungi are commonly used as species standards when comparing the potential of new strains to produce lignin-degrading enzymes [12,13]. Previously, the ability of 600 white-rot Indonesian fungal sources to biobleach Acacia oxygen-delignified kraft pulp (A-OKP) was screened, with P. chrysosporium and T. versicolor as standard fungi [14]. The biobleaching in vivo activity of the selected fungal strains Irpex lacteus KB-1.1 and Lentinus tigrinus LP-7 was higher than that of P. chrysosporium and T. versicolor.…”
Section: Introductionmentioning
confidence: 99%